Pectoralis major tendon tears: a biomechanical study to analyze the influence of intratendinous suture distance on repair stability - Wahlers, Christopher; Hoffeld, Kai; Hockmann, Jan; Müller, Lars Peter; Leschinger, Tim; Hackl, Michael (Journal of shoulder and elbow surgery, 2025)
Background - Tendon tears of the pectoralis major (PM) are uncommon and can be challenging to manage. The lack of consensus on optimal repair methods for PM tendon tears prompts further investigation. - Methods - Twenty four fresh-frozen shoulder specimens were used for this biomechanical in-vitro investigation. After simulating complete tears of the PM at its insertion, repair was performed with 3 suture anchors using a locking whipstitch technique of the PM tendon over a length of 2 (group 2), 4 (group 4), or 6 cm (group 6), 8 specimens per group. Incremental cyclic loading of the specimens was performed from 10 to 200 N and the number of cycles and the force until failure (5-mm gap formation at the tendon-bone interface) occurred were analyzed. - Results - The mean number of cycles until failure was 89 for group 2, 81 for group 4, and 175 for group 6. Group 6 withstood significantly more loading cycles than groups 2 and 4 (P = .019). The mean force until failure was 63.8 N for group 2, 67.5 N for group 4, and 110.0 N for group 6. Group 6 reached significantly higher failure loads when compared to groups 2 and 4 (P ≤ .014). - Conclusions - This study contributes valuable insights into the optimal suture technique for repair of PM tendon tears, highlighting the biomechanical stability associated with varying lengths of locking whipstitches. The results of this investigation show that a locking whipstitch of the PM tendon over a length of 6 cm provides superior biomechanical properties at time zero. Clinical data are necessary to evaluate its relevance on the functional patient outcome.